An artificial intelligence applications into Software Defined Networking - Abdul Mohssen Jaber Abdul hossen,Mohamed Najem Abdual , MohammadQassim (International Journal of Advanced Science and Technology, 2020)
Background/objectives:The presented study will examine the applications regarding to An Aritifical Intelligentin to Software Defined Network  paradigm that is considered as part of past attempts for giving the networks of computer the capability of being programmed depending on separation between controlas well as the forwarding planes. With regard to the Software Defined Network method, controller will be specifying the central brain regarding network that result in sophisticated flexibility level as well as network intelligence.